Kekuatan Hukum Pelekatan Sidik Jari Penghadap Oleh Notaris Pada Minuta Akta - Dewi, Wulan Wiryantari; R, Ibrahim (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
The notary's role is to provide legal protection to the people who use his services. The presence of a Notary is indispensable for the community concerned to hold a legal relationship with other individuals so that the Notary may also be liable. In the provisions of Article 16 paragraph (1) letter c of the Amendment Law, it is stipulated that in carrying out his position, the Notary is required to attach fingerprints on the minutes of the deed, giving rise to various polemics, because the said provisions do not stipulate further if in this case the smoker suffers from finger defects or events that result in damage to fingerprints which makes the investigator unable to put his fingerprint. The purpose of this research is to find out how the efforts that can be done by a notary against those who are unable to put fingerprints and the legal consequences of the absence of fingerprints against the strength of the deed. This research is a type of normative legal research. The results of this study indicate that efforts can be made by a notary if there are those who suffer from finger defects or experience events that cause fingerprint damage so that they cannot attach their fingerprints to the minutes of the deed, the relevant Notary can explain the matter at the end of the deed. he made it because the fingerprints attached to the address are an act that is required to a notary that can lead to administrative sanctions as contained in the Amendment Law. Due to the legal absence of fingerprints attached to the strength of the deed that is the deed made by the relevant Notary Public remains an authentic deed even though the fingerprints of the tappers are not attached based on Article 1869 of the Civil Code and the deed is valid and legally binding as long as the provisions contained in Article 1320 are fulfilled Civil Code.